Zad. 38
a) 3 * (2x + 1) = 4 * (x - 2)
6x + 3 = 4x - 8
6x - 4x = -8 + 3
2x = -5
x = -2,5
b) 2 * (2x - 2) = 3 * (3x + 2)
4x - 4 = 9x + 6
4x - 9x = 6 + 4
-5x = 10
-x=2
x = -2
c) 1,2 * (6x - 1) = 2,3 * (x+1)
7,2x - 1,2 = 2,3x + 2,3
72x - 12 = 23x + 23
72x - 23x = 23 + 12
49x = 35
7x = 5
x = 5/7
d) -x * (1 - 6x) = 2x * (3x - 1)
-x + 6x ² = 6x² - 2x
-x + 2x = 6x² - 6x²
x=0
Zad. 39
(3 + x) / (5 + x) = 2/3
2(5 + x) = 3(3 + x)
10 + 2x = 9 + 3x
10 - 9 = 3x - 2x
x = 1
odp. do mianownika i licznika należy dodać 1.